2022
DOI: 10.1002/pbc.29666
|View full text |Cite
|
Sign up to set email alerts
|

Living in an online world: Social media experiences of adolescents and young adults with cancer

Abstract: Background Despite widespread use, little is known about how adolescents and young adults (AYA) with cancer use social media (SM). This research characterized use and self‐reported SM experiences among AYA with cancer. Procedure AYA, aged 12‐26 years, receiving cancer care completed a mixed‐methods survey regarding SM experiences. Clinical information was obtained from the electronic medical record. Data were analyzed with descriptive statistics, t tests, and qualitative content analysis. Results Thirty‐nine A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…This discrepancy highlights the importance of addressing the distinct needs of BIPOC AYA patients as a specific group while keeping in mind that broader interventions may benefit BIPOC AYA patients as well as others. The utility of optimizing social media to expand outreach in these groups is consistent with prior studies showing the efficacy of social media in disseminating cancer-related information among AYA cancer patients [ 31 , 46 ].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This discrepancy highlights the importance of addressing the distinct needs of BIPOC AYA patients as a specific group while keeping in mind that broader interventions may benefit BIPOC AYA patients as well as others. The utility of optimizing social media to expand outreach in these groups is consistent with prior studies showing the efficacy of social media in disseminating cancer-related information among AYA cancer patients [ 31 , 46 ].…”
Section: Discussionsupporting
confidence: 77%
“…The Delphi method is a mixed methods research technique used to achieve consensus agreement on a specific topic by soliciting the anonymous opinions of subject matter experts via iterative survey rounds ( Figure 2 ) [ 29 , 30 ]. The current research was an electronic Delphi (e-Delphi) study conducted via online surveys and digital platforms that responded to AYAs' accessibility preferences [ 31 ]. The investigators surveyed a panel of experts defined as self-identified BIPOC patients diagnosed with cancer between ages 15 and 39 years.…”
Section: Methodsmentioning
confidence: 99%
“…It is estimated that China’s older population over 60 will exceed 358 million by the end of 2030 ( Peng and He, 2017 ), posing huge challenges to the supply of medical and public services. Depression is a prevalent condition and a public health concern ( Reuman et al, 2022 ), there is a growing body of evidence suggesting that depression has a negative impact on the survival of older adults ( Zivin et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…[59][60][61] Selfassessment tools are also featured on Breas tcanc er.org Remedies for anxiety and depression include a wide range of options. Some cancer patients will improve with psychoeducational support groups, 62 online communities and digital tools, [63][64][65] yoga, 66 or mindfulness-based interventions, 67 including internet-delivered mindfulness-based cognitive therapy. 68 Other patients may require more intensive psychotherapy or pharmacotherapy, including benzodiazepines and anti-depressants.…”
Section: Next Stepsmentioning
confidence: 99%